KAJIAN PENGARUH PENGGUNAAN SURFAKTAN NON IONIK TERHADAP EFISIENSI PENJERAPAN SISTEM NIOSOM PADA SEDIAAN TOPIKAL - Nur Musdalifah; Rakhma Rakhma; Yuli Ainun Najih (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2022)
Some of active ingredients in formulation of topical preparations having problem at solubility. Therefore, an effort was made to overcome this problem, thats is a Novel Drug Delivery System (NDDS) for topical route that can increase solubility and stability active ingredients. Niosomes as a modern drug delivery system consist of a combination of non-ionic surfactant vesicles, cholesterol and other additives. In the formulation of niosomes, non-ionic surfactants have an important role because they do not have a charged nucleus in them, non-ionic surfactants have an amphiphilic molecular structure with hydrophilic heads and hydrophobic tails that are water soluble and organically soluble. Types of non-ionic surfactants that are often used in the formulation of niosomes are span and tween. Span 60 has the highest active ingredient entrapment efficiency compared to other types of surfactants. The purpose of this study was to determine the effect of non-ionic surfactants used in formulation of niosomes system on the entrapment efficiency active. This research was conducted using an iterative study method using 15 article about effect using non-ionic surfactants on entrapment efficiency niosome system on the active ingredients of topical formulations. The databases used are NCBI, MDPI, Elsevier, Google Scholar, and Science direct. The studies were screened according to the inclusion criteria that had been determined. Based on the results of this literature study, it can be concluded that the addition of variations type and concentration of non-ionic surfactants at niosome system has an influence on the quality of entrapment efficiency active ingredient.